G266(P) A regional quality improvement project for congenital cytomegalovirus (cCMV) associated sensorineural hearing loss leading to improved prioritisation of finite resources during the covid-19 pandemic. (25th October 2020) - Khan, Z; Brown, R; Banks, V; Holland Brown, T
Abstract : Background: Congenital CMV [cCMV] is a leading cause of hearing loss and childhood disability. Recent research demonstrated children's long-term outcomes could be improved with antiviral treatment offered within the first month of life. During the COVID-19 pandemic, national hearing screening guidance promoted prioritisation of face-to-face diagnostic auditory brainstem response [ABR] in infants with cCMV. Aim: To identify babies with cCMV and hearing loss within 1 month of life to ensure: Greater certainty of the diagnosis of cCMV. Early paediatric referral for identification and management of cCMV Timely consideration of treatment Method: A truly joined-up, multidisciplinary approach was taken across the region (newborn hearing screeners, audiologists, ENT surgeons, virologists, neonatologist, paediatricians, ophthalmologists). Targeted cCMV testing was undertaken by newborn hearing screeners in all babies who 'failed' their otoacoustic emission and automated ABR. CMV positive babies were referred urgently to paediatricians to consider management and treatment within 1 month of life. We derived data on the timing of cCMV testing in the months before and then during the pandemic. Results: Regional hospitals worked together to write the East of England CMV guidelines which were then ratified. https://www.networks.nhs.uk/nhs-networks/eoe-neonatal-odn/guidelines/current-guidelines/congenital-cmv-guideline Following implementation in early 2019, Addenbrookes Hospital data showed that babies undergoing hearing screening during the pandemic could be prioritised according to national guidance for definitive ABR testing Conclusion: CMV saliva swabs for babies born with hearing loss was implemented across the East of England region using a wide multidisciplinary approach. In the pandemic, this enabled prioritisation of diagnostic ABR testing in babies with cCMV and hearing impairment according to national guidance.